2009
DOI: 10.1021/jo802628z
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Cu-Catalyzed Protodecarboxylation of Aromatic Carboxylic Acids

Abstract: An effective protocol has been developed that allows the smooth protodecarboxylation of diversely functionalized aromatic carboxylic acids within 5-15 min. In the presence of at most 5 mol % of an inexpensive catalyst generated in situ from copper(I) oxide and 1,10-phenanthroline, even nonactivated benzoates were converted in high yields and with great preparative ease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
70
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(78 citation statements)
references
References 21 publications
6
70
1
1
Order By: Relevance
“…This seminal report paved the way for other similar methods to be developed with changes to the ligand system allowing for lower temperatures 18 to be used and microwave heating giving a reduction in reaction times. 19 The increased reactivity of orthosubstituted substrates provoked an investigation into the mechanism of these reactions. Through DFT studies the groups of Su 20 and Gooßen 21 found a plausible transition state 8 in which the Cu inserts into the aryl carboxyl bond (Scheme 3A).…”
Section: Transition Metal-promoted Protodecarboxylationmentioning
confidence: 99%
“…This seminal report paved the way for other similar methods to be developed with changes to the ligand system allowing for lower temperatures 18 to be used and microwave heating giving a reduction in reaction times. 19 The increased reactivity of orthosubstituted substrates provoked an investigation into the mechanism of these reactions. Through DFT studies the groups of Su 20 and Gooßen 21 found a plausible transition state 8 in which the Cu inserts into the aryl carboxyl bond (Scheme 3A).…”
Section: Transition Metal-promoted Protodecarboxylationmentioning
confidence: 99%
“…This reaction has been tested previously only with molecular copper complexes, copper salts, but not with nanoscale catalysts and none of the previous catalyst systems was suitable for recycling 56,57 (Scheme 2). …”
Section: Protodecarboxylation Reactionmentioning
confidence: 99%
“…48,52 A challenging reaction for the evaluation of nanoscale catalysts is the protodecarboxylation reaction. 56,57 Notably, this reaction has not been evaluated yet for nanoscale catalysts in ionic liquids. Usually the model system for copper catalysts is the Ullmann reaction.…”
mentioning
confidence: 99%
“…Achieving such a balance in the microwave is not an easy task, knowing from previous investigations that microwave irradiation accelerates the Cucatalyzed decarboxylation step to a much larger extent than the cross-coupling step. [22] We were thus not surprised that initial attempts at simply transferring the existing procedures for the cross-coupling, for example, of potassium 2-nitrobenzoate with 4-tolyl bromide, to the microwave failed (see below). Still, we were motivated to continue this effort because, in theory, microwave technology perfectly meets the requirements of decarboxylative couplings on the laboratory scale, combining efficient heating with the possibility to use small, contained vessels certified for pressure reactions.…”
Section: Introductionmentioning
confidence: 99%